Students' Collaborative Writing Method in Pre-Writing Phase - Kartika Dewi Rahayu (Institut Agama Islam Negeri Palopo, 2020)
In a pre-writing phase, students need their creativity to put ideas into words. Students need to use what they listen to and what they read as information to start to write. This study reports the findings on the implementation of the collaborative writing method by an English teacher in teaching writing in the pre-writing phase and students' perceptions in the pre-writing phase using the collaborative writing method. This research uses descriptive qualitative research. Participants in this study were nine students and teachers at SMK in Karawang. Data collection was carried out through reflective journals, interviews, and documentation. The results of the study found that the collaborative writing method was an effective method for use in writing classes. The collaborative writing method can be implemented in teaching writing in the pre-writing phase. The results showed that the students were very enthusiastic, interested, and made the learning process fast. Students' perceptions of learning to write in the pre-writing phase using the collaborative writing method are that students find it easier to express their thoughts in the learning process and there is cooperation in groups that accelerate the time when doing their assignments helps them during the learning process.